Growth and characterisation of quantum materials nanostructures - Schönherr, P (2016)
The three key areas of this thesis are crystal synthesis strategies, growth mechanisms, and new types of quantum materials nanowires. The highlights are introduction of a new catalyst (TiO2) for nanowire growth and application to Bi2Se3, Bi2Te3, SnO2, and Ge nanowires; demonstration of step-flow growth, a new growth mechanism, for Bi2Te3 sub-micron belts; and the characterisation of the first quasi-one dimensional topological insulator (orthorhombic Sb-doped Bi2Se3) and topological Dirac semimetal nanowires (Cd3As2). Research into new materials has been one of the driving forces that have contributed to the progress of civilisation from the Bronze Age four thousand years ago to the age of the semiconductor in the 20th century. At the turn to the 21st century novel materials, so-called quantum materials, started to emerge. The fundamental theories for the description of their properties were established at the beginning of the 20th century but expanded significantly during the last three decades based, for example, on a new interpretation of electronic states by topological invariants. Hence, topological insulator (TI) materials such as mercury-telluride are one manifestation of a quantum material. In theory, TIs are characterised by an insulating interior and a surface with spin-momentum locked conduction. In real crystals, however, the bulk can be conducting due to crystal imperfections. Nanowires suppress this bulk contribution inherently by their high surface-to-volume ratio. Additionally, trace impurity elements can be inserted into the crystal to decrease the conductance further. These optimised TI nanowires could provide building blocks for future electronic nanodevices such as transistors and sensors. Initial synthesis efforts using vapour transport techniques and electronic transport studies showed that TI nanowires hold the promise of reduced bulk contribution. This thesis expands the current knowledge on synthesis strategies, crystal growth mechanisms, and new types of quantum materials nanowires. Traditionally, gold catalyst nanoparticles were used to grow TI nanowires. We demonstrate that they are suitable to produce large amounts of nanowires but have undesired side-effects. If a metaloxide catalyst nanoparticle is used instead, quality and even quantity are significantly improved. This synthesis strategy was used to produce a new TI which is built from chains of atoms and not from atomic layers as in case of previously known TIs. The growth of large nanowires with a layered crystal structure leads to step-flowgrowth, an intriguing phenomenon in the growth mechanism: New layers grow on top of previous layers with a single growth frontmoving fromthe root to the tip. These wires are ideal for further electronic characterisation that requires large samples. The nanowire growth of tin-oxide will also be discussed, a side project that arose from my growth studies, which is useful for sensor applications. Under certain conditions it forms tree-like structures in a single synthesis step. All of the aforementioned growth studies are carried out at atmospheric pressure. A separate growth study is carried out in ultra-high vacuum to assess the transferability of the growth process towards the cleanliness requirements of the semiconductor industry. If two quantum materials are joined together, exotic physics may emerge at the interface. One of the goals of TI research is the experimental observation of Majorana fermions, exotic particles which are their ownantiparticles with potential applications in quantum computing that may appear in superconductor/TI hybrid structures. We have synthesised such structures and initial characterisation suggests that the resistivity increases when they are cooled below the critical temperature of the superconductor. Beyond TIs, a new type of quantum material, called a topological Dirac semimetal, opens new realms of exotic physics to be discovered. Nanowires are grownfroma material which has recently been discovered to be a topological Dirac semimetal. Their growth mechanism is characterised and an extremely high electron mobility at room temperature is measured. The contribution of this thesis to the field is summarised in Fig. 1. Its core is the study of the growth mechanism of quantum materials which will be vital for future development of applications and fundamental research.